Effectiveness of Video-Based Educational Intervention on Knowledge, Attitude, and Practice (KAP) of COVID-19 Health Care Workers: Lesson for Future Pandemic Preparedness - Gupta, Surbhi; Goswami, Binita; Madhu, S.V. (Annals of the National Academy of Medical Sciences (India), 2023)
Introduction As we have seen from the previous health emergencies, most recently the COVID-19 pandemic, public health education is often the first line of defense in any disease prevention. Through a short educational video intervention, this study aims to improve the awareness regarding COVID-19 infection control practices to be followed in a clinical laboratory.Methods An online pre- and posttest survey was conducted. After pretest, an educational video was shared among the study participants followed by post test survey. This questionnaire contains items on three domains: knowledge, safe laboratory practices, and attitude.Results Significant improvement occurred in all three domains in study participants post educational intervention.Conclusion Simple educational video intervention can substantially improve the readiness of frontline workers to deal with any kind of pandemic situation.
Keywords: COVID-19; health care personnel; medical education; preparedness